2016
DOI: 10.1016/j.neuroimage.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

How do negative emotions impair self-control? A neural model of negative urgency

Abstract: Self-control often fails when people experience negative emotions. Negative urgency represents the dispositional tendency to experience such self-control failure in response to negative affect. The neural underpinnings of negative urgency are not fully understood, nor is the more general phenomenon of self-control failure in response to negative emotions. Previous theorizing suggests that an insufficient, inhibitory response from the prefrontal cortex may be the culprit behind such self-control failure. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 40 publications
(49 reference statements)
10
93
0
4
Order By: Relevance
“…This parallels the model put forth by Chester and colleagues (37) of negative urgency’s relationship with response inhibition (as measured by neural responsiveness during an emotionally valenced Go/No-Go task) and real-world substance abuse. They observed greater recruitment of PFC regions during negatively-valenced response inhibition for participants high in negative urgency (without behavioral performance differences), and this same pattern observed in the anterior insula predicted greater substance abuse measured one month and one year after scanning.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This parallels the model put forth by Chester and colleagues (37) of negative urgency’s relationship with response inhibition (as measured by neural responsiveness during an emotionally valenced Go/No-Go task) and real-world substance abuse. They observed greater recruitment of PFC regions during negatively-valenced response inhibition for participants high in negative urgency (without behavioral performance differences), and this same pattern observed in the anterior insula predicted greater substance abuse measured one month and one year after scanning.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, a comprehensive investigation of the role of impulse control in risky sexual behavior should incorporate personality measures as well as neural and behavioral ones. One relevant study (37) has integrated the measurement of negative urgency with behavioral and neural responses to the Go/No-Go response inhibition task and found that neural activity during response inhibition predicted subsequent substance abuse in individuals high in negative urgency, but no research has synthesized all of these components in relation to real-world sexual risk taking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although not previously hypothesized, research suggests that negative urgency is associated with increased reward circuitry responding, including (1) increased activation in the medial prefrontal cortex during the Monetary Incentive Delay Task (Weiland et al, 2014), (2) increased VMPFC activation to alcoholic drink aromas in social drinkers (Cyders et al, 2014), and (3) increased caudate nucleus activation to alcohol images (Chester et al, under review-a). This latter finding suggests that urgency might relate to an increase in attention to and salience of rewarding cues in the environment, which then cue subsequent craving that is not as effectively modulated via top-down circuitry, perhaps due to excessive activation of and fatigue in inhibitory brain regions (Chester et al, under review-b). Strikingly, in two of these studies, the relationship between increased responses to emotional stimuli and increased responses to alcohol cues and risk-taking was mediated by negative urgency (Cyders et al, 2013, 2014), suggesting that physiological hyperreactivity to emotional stimuli and reward cues is related to later risk taking in part by increasing the tendency toward rash action in negative emotional states.…”
Section: Empirical Tests Of Urgency Theory Hypothesesmentioning
confidence: 99%
“…Although some reports suggest that negative urgency is unrelated to the intensity or frequency of self-reported emotion (e.g., Cyders et al, 2009; Cyders and Coskunpinar, 2010), others suggest a relationship between negative urgency and physiologic correlates of emotional reactivity (e.g., Cyders et al, 2014), which then subsequently influence alcohol-seeking (e.g., Carney et al, 2000; Steptoe and Wardle, 1999). Proposed mechanisms include increased emotional reactivity (e.g., Albein-Urios et al, 2013; Cyders et al, 2014), increased attention to and salience of reward cues (e.g., Chester et al, in press ; Cyders et al, 2014), increased reward circuitry activation (e.g., Wilbertz et al, 2014; Xue et al, 2010), and decreased ability to regulate emotional experiences (e.g., Hoptman et al, 2014; Muhlert and Lawrence, 2015). However, research has yet to directly examine these factors, perhaps in part because of limitations in the ability to measure alcohol related behaviors in experimental contexts.…”
Section: 0 Introductionmentioning
confidence: 99%
“…We hypothesized that greater negative urgency would be related to: 1) greater mood change from negative mood induction (e.g., Albein-Urios et al, 2013; Cyders et al, 2014); 2) greater cortisol release to negative mood induction (increased physiologic reactivity in Cyders et al, 2014); 3) greater alcohol craving in response to an alcohol prime following negative mood induction (e.g., Chester et al, in press ; Cyders et al, 2014); 4) greater cortisol release to the alcohol prime (e.g., increased physiologic reactivity in Cyders et al, 2014); 5) higher peak BrAC in the negative mood session (e.g., Coskunpinar et al, 2013; Settles et al, 2010); and 6) more work for alcohol rewards in the negative mood session (e.g., Carney et al, 2000; Steptoe and Wardle, 1999). …”
Section: 0 Introductionmentioning
confidence: 99%